Sport selection in under-17 male roller hockey - Coelho e Silva, M. J.; Vaz, V.; Simoes, F.; Carvalho, H. M.; Valente-dos-Santos, J.; Figueiredo, A. J.; Pereira, V.; Vaeyens, R.; Philippaerts, R.; Elferink-Gemser, M. T.; Malina, R. M. (Journal of Sports Sciences, 2012)
Characteristics of 32 international and 41 local under-17 (U-17) (14.5-16.5 years) roller hockey players were considered in the context of discrimination by competitive level using training history, anthropometry, skeletal maturation, and several laboratory and field performance tests. More international (42%) than local (22%) players were advanced in maturity status. International players had slightly less hockey experience (years), but had more practice sessions and match time (minutes) during the season. Local players were shorter and attained better performance in the 25-m dash, while international players performed better in sit-ups, ball throw and 20-m shuttle run. The fatigue index derived from the Wingate anaerobic test was higher among local players, while peak torques of knee extension and flexion were greater in international players. Stepwise discriminant function correctly classified 85% of players by competitive level based on grip strength, ratio of eccentric and concentric knee extension, number of training sessions, playing time and fatigue index. The results suggested an interaction among strength, anaerobic fitness and training plus game time as factors in discriminating international from local level players and by inference in the selection and development of youth roller hockey players.